A New Source of Diterpene Lactones From Andrographis paniculata (Burm. f.) Nees—Two Endophytic Fungi of Colletotrichum sp. With Antibacterial and Antioxidant Activities - Li, Na; Xu, Dan; Huang, Rui-Hua; Zheng, Jian-Yun; Liu, You-Yan; Hu, Bin-Sheng; Gu, Yuan-Qin; Du, Qin (Frontiers in Microbiology, 2022)
Endophytic fungi of medicinal plants are abundant and their metabolites often have antioxidant, antibacterial, and antitumor effects and can produce secondary metabolites identical or similar to those of their hosts, which can mitigate the problem of insufficient supply of medicinal plants. In this study, we screened endophytic fungi for strains that produce the same diterpene lactones as Andrographis paniculata based on their biological activity. Firstly, the dominant group of endophytic fungi of Andrographis paniculata was screened and pathogenicity was studied using Koch's rule. Secondly, DPPH, ABTS, OH, PTIO radical scavenging, and FRAP assays were used to detect the antioxidant activity of the extracellular extracts of the strains, and total phenol and total flavonoid contents of the strains with high antioxidant capacity were determined. S. aureus, B. subtilis, E. coli, and P. aeruginosa were used to determine the antibacterial activity of the mycelial extracts of the strains. Finally, the secondary metabolites of the mycelial extracts of the strains were examined by high-performance liquid chromatography. The results showed that 32 strains of Andrographis paniculata were relatively isolated >70% and non-pathogenic. Extracellular extracts of strains AP-1 and AP-4 showed vigorous antioxidant activity, and AP-4, AP-12, AP-47, and AP-48 showed antibacterial activity against four strains of bacteria. The HPLC results indicated that the mycelial extracts of AP-4 and AP-12 contained diterpene lactones. The two endophytic fungi were recognized as Colletotrichum sp. The study successfully obtained diterpene lactones from the endophytic fungus of Andrographis paniculata and confirmed the feasibility of using endophytic fungal strains to produce active substances consistent with the host. It was also useful for exploring endophytic fungi and medicinal plants The relationship provides theoretical guidance.